Quadrilateral Cell-Based Anisotropic Adaptive Solution for the Euler Equations (Communications in Computational Physics, 2011)
An anisotropic solution adaptive method based on unstructured quadrilateralmeshes for inviscid compressible flows is proposed. The data structure, the directionalrefinement and coarsening, including the method for initializing the refinednew cells, for the anisotropic adaptive method are described. It provides efficient highresolution of flow features, which are aligned with the original quadrilateral meshstructures. Five different cases are provided to show that it could be used to resolvethe anisotropic flow features and be applied to model the complex geometry as well asto keep a relative high order of accuracy on an efficient anisotropic mesh.